APLIKASI PENCARIAN TEMPAT WISATA, HOTEL DAN KULINER BENGKALIS MEMANFAATKAN TEKNOLOGI GPS BERBASIS ANDROID - Lidya Wati; Devit Satria (Jaringan Sistem Informasi Robotik-JSR, 2019)
Information about tourist attractions, hotels and culinary Bengkalis not yet complete and detailed. So that the local tourists who visit Bengkalis less get the information. For that purpose, it is designed the search application of tourist, hotel and culinary place in Bengkalis by utilizing Global Positioning System (GPS) technology on android device and generate a website which is used to input all information needed by android application to database server by admin. This application is designed using Java programming language and MySQL as database. System design uses Unified Modeling Language (UML) which consists of use case diagram, activity diagram, sequence diagram and class diagram while database design using entity relationship diagram. The results achieved is a search application of tourist attractions, hotels and culinary in Bengkalis by utilizing Global Positioning System (GPS) technology found on android device to facilitate users to get information and search for tourist attractions, hotels and culinary in Bengkalis.